the effect of both models of Good Lavoie and Martorella in acquiring the rhetorical concepts and the keep for the literary study fifth class female students . (Journal of the College of Basic Education, 2020)
The present study aimed to identify the effect of both models of Good Lavoie and Martorella in acquiring the rhetorical concepts and the keep for the literary study fifth class female students. The research's sample consisted of (91) students, The researcher formulated (65) behavioral goals according to Bloom’s classification in the knowledge field within its six levels. After processing the data statistically using one-way analysis of variants, the study concluded 1-superiority of the first experimental group of female students who have studied rhetoric and applying by using (Good Lavoie) model on the controlling group female students who have in acquiring rhetorical concepts and the keep.2-Superiority of the second experimental group which have studied rhetoric and applying by using (Martorella) model on the controlling group female students which have in acquiring rhetorical concepts and the keep.